The Influence of Online Game on the Learners’ Arabic Vocabulary Achievement - Kamal, Helmi (Universitas Islam Negeri Raden Intan Lampung, 2021)
Online game is suggested as a medium that can encourage learners' acquisition of Arabic vocabulary. This research aimed to find out the learners’ vocabulary achievement before applying online game to the learners and to describe the usage of online game in improving learners’ vocabulary achievement effectively. This research used Classroom Action Research. There were 30 learners involved. Teaching processes consisted of two-cycle. Interviews, observation, tests, and documentation were the instruments of this research. The results of the tests were analyzed by using SPSS 20; the results of the interview and observation were analyzed qualitatively. The author found that online game improves learners’ vocabulary. The average score in cycle I was better than the average score in cycle II. The Pretest results in cycle I showed the greatest score obtained by the learners was 76. While in the Post test of the cycle I, the greatest score obtained by the learner was 90. Whereas in cycle II, the greatest score obtained by the learners was 100. Based on the observation, the learners were more excited on studying and focus on finishing their task; the learners could understand well the subject was given, and the learners were more enthusiastic in memorizing vocabulary. The author had successfully provided a new experience for learners who always learn conventionally by involving into the appealing and interactive online game-based learning atmosphere. The author hoped this research could be guidance for the effectuality of the next Arabic language learning through the online game in the class.